1998
DOI: 10.1046/j.1365-3024.1998.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE responses in the serum and gastric lymph of sheep infected with Teladorsagia circumcincta

Abstract: The IgE response of naive or previously infected sheep to 50,000 infective larvae of Teladorsagia circumcincta was monitored in serum and gastric lymph using a monoclonal antibody generated to recombinant ovine IgE in a dot blot assay. In 4/5 naive sheep, lymph and serum IgE concentrations increased from days 8 and 14 after infection, respectively. In most previously infected sheep, the IgE response to challenge was more rapid, although not necessarily greater than that following a primary infection. IgE conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Studies on IgE response in ruminant were as yet restricted to sheep and cattle. Thus, in sheep increased total and nematode-specific serum IgE levels after gastrointestinal nematode infection have been reported in many studies (Huntley et al, 1998;Pernthaner et al, 2005). Furthermore, a negative correlation between worm counts and total serum IgE levels was found in sheep parasitized with H. contortus (Kooyman et al, 1997).…”
Section: Discussionmentioning
confidence: 71%
“…Studies on IgE response in ruminant were as yet restricted to sheep and cattle. Thus, in sheep increased total and nematode-specific serum IgE levels after gastrointestinal nematode infection have been reported in many studies (Huntley et al, 1998;Pernthaner et al, 2005). Furthermore, a negative correlation between worm counts and total serum IgE levels was found in sheep parasitized with H. contortus (Kooyman et al, 1997).…”
Section: Discussionmentioning
confidence: 71%
“…(49) and Kooyman et al. (8) and several studies have shown that sheep infected with GIN have increased total and worm‐antigen‐specific IgE (8,12,13,50,51). Mean serum IgE levels in our lambs exceeded 60 ng/mL through 16 days p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Host immunoglobulin (Ig)E responses have been associated with helminth infections for a long time (1) Studies on IgE responses in ruminants were restricted to sheep and cattle. Sheep IgE levels in serum or lymph increased after infection with gastrointestinal nematodes (2)(3)(4)(5)(6). In one of these studies (4), a correlation between total serum IgE and protection against Haemonchus contortus infection was found (4).…”
Section: Introductionmentioning
confidence: 99%